2019
DOI: 10.1016/j.joule.2019.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Design Rules for Membranes from Polymers of Intrinsic Microporosity for Crossover-free Aqueous Electrochemical Devices

Abstract: Placement of amidoxime functionalities within the pores of microporous polymer membranes yields a new family of selective membranes for aqueous electrochemical cells-which we call AquaPIMs. At high pH, where amidoximes are ionized, AquaPIM membranes feature concomitantly high conductivity and transport selectivity when compared to other membranes, including Nafion. Design rules are laid out, tying membrane architecture and pore chemistry to membrane stability, conductivity, and transport selectivity in aqueous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 99 publications
1
85
0
Order By: Relevance
“…Chemical cross‐linking can be used to restrict pore swelling and to control the pore size of the polymer separators. By using membranes composed of polymers with intrinsic microporosity (PIMs), crossover‐free flow batteries may be realized …”
Section: Organic Materials As Redox Electrolytes For Flow Batteriesmentioning
confidence: 99%
“…Chemical cross‐linking can be used to restrict pore swelling and to control the pore size of the polymer separators. By using membranes composed of polymers with intrinsic microporosity (PIMs), crossover‐free flow batteries may be realized …”
Section: Organic Materials As Redox Electrolytes For Flow Batteriesmentioning
confidence: 99%
“…Helms et al evaluated the performance of hydrophilic amidoxime-containing PIM membrane (Figure 1b, AO-PIMÀ A) in a Zn-based aqueous electrochemical cell. [24] Ionizable amidoxime moieties and the high micro-porosity endow membrane with high conductivity, especially under strongly alkaline conditions. AO-PIMÀ A1 membrane exhibits a satisfying ionic conductivity of 16.9 mS cm À 1 in 40 % aqueous KOH (w/w), which is much higher than that of Nafion 212 (below 1 mS cm À 1 ).…”
Section: Hpims For Aqueous Redox Flow Batteriesmentioning
confidence: 99%
“…The surface area of AO-PIM-1 can be tuned by appending 2D contortion sites such as bridged bicyclic structure to the polymer backbones ( Figure 1). [24] With the same method, Tan et al successfully modified the spirobifluorene-containing PIM (PIM-SBF) and obtained AO-PIM-SBF. [25] The hydrophilic amidoxime group can be either positively charged or negatively charged in aqueous solutions, depending on pH.…”
Section: Post-synthetic Modification To Introduce Hydrophilic Moietiesmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Several recent studies reported the use of PIMbased separator membranes for rechargeable batteries: a pristine PIM-1 membrane was used to block shuttling of polysulfur ions in Li-S battery; 22 Tröger's base 23 and N-spirocyclic quaternary ammonium 24 polymer membranes showed the ability to conduct hydroxide (OH À ) or proton (H + ); an amidoximefunctionalized PIM membrane was used to construct solvent crossover-free Zn-based redox ow batteries. 25 It is worth noting that these works mainly focused on the ionic conductivity of the membranes, whereas how to incorporate the "solvent molecule blocking" ability in a polymeric membrane has not been explored and remains a challenge, which requires rational design at the molecule level to achieve precise control of microstructure and functionality of the membrane.…”
Section: Introductionmentioning
confidence: 99%